Perbandingan Desain Kontrol Fuzzy Logic Controller (FLC) dan Pole Placement untuk Sistem Dua Tangki yang Saling Berinteraksi - Sulis Rizkiatul Fitri; Mardlijah (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2024)
The interacting two-tank system provides important benefits in maintaining water quality, preventing pollution, and optimizing the distribution of clean water in various industrial applications. Therefore, it is important to control the water level for the interacting two-tank system in order to generate drinking water of high quality that is suitable for consumption for the community and other living beings. In this article, we analysis the stability and controllability the model of the interacting two-tank system. The result of the analysis prove that the system is stable and controllable. Furthermore, to control the water level, we using two methods that is Fuzzy Logic Controller (FLC) and Pole Placement. We compared two control methods and examined which one provided faster stability and more robust from disturbances. Based on the simulation output, it can be concluded that Fuzzy Logic Controller (FLC) performs better than Pole Placement. Fuzzy Logic Controller (FLC) enables the system to achieve faster stability without overshoot and is more robust against disturbances. However, the simulation waiting time for Pole Placement is faster than FLC